P317 FATAL EVOLUTION IN A YOUNG WOMAN DUE TO AMYLOIDOSIS HEART FAILURE IN A RARE MULTIPLE MYELOMA DISEASE. (18th May 2022) - Magistro, A; Cicco, S; Marozzi, M; Narcisi, V; Carrieri, A; Longo, S; Giliberti, T; Melaccio, A; Solimando, A; Lauletta, G; Vacca, A; Ria, R
Abstract: Introduction: Immunoglobulin (Ig) D (IgD) monoclonal gammopathy is a rare subtype of multiple myeloma (MM) associated with a worse prognosis. Ig light chains amyloidosis is a disorder characterized by extracellular deposition of Ig light chains in various tissues, leading to organ dysfunction. Case: A 29–year–old woman was admitted for dyspnea and tachycardia for moderate efforts. Lab revealed hypogammaglobulinemia with a monoclonal IgD K paraprotein. There was an increase in K free chains, with a dramatic increase in K/λ free chains Ratio. Proteinuria was 1360 mg/24h with a free K chains Bence Jones Protein. An increase in values of Troponin–I (137, 5 pg/mL) and NT–proBNP (12527 pg/mL) pointed towards heart involvement. Furthermore, the ECG showed low voltages in the peripheral leads. Echocardiogram showed a moderate concentric left ventricular hypertrophy with diffused myocardial speckled pattern, an ejection fraction (EF) of 53% and PAPs of 71 mmHg and pericardial effusion. Chest CT scan showed bilateral pleural effusion. Spine MRI and whole body PET/CT indicated areas of osteolytic lesions. Plasma cells infiltration (85% CD138, MUM1 and K chains positivity) was present at bone marrow biopsy. Amyloid deposition was detected in abdominal fat tissue sample. Total bone scintigraphy excluded a transthyretin heart deposition. Thus, amyloidosis associate to IgD MM was diagnosed. In few days heart failure worsened (hs–cTnI 156, 6 pg/mL; NT–proBNP 26583 pg/mL, EF 48%, ) and the patient began complaining non–productive cough, dyspnea, and columnar edema of the lower limbs. She was not eligible for bone marrow transplantation, so daratumumab, bortezomib, melphalan and prednisone were administered. Despite serological improvement after a short five days course of therapy, she worsened with a further reduction of EF (35%). Blood gas analysis showed hypoxemia and lactate increase quickly turned into a cardiogenic shock. She died by cardiac arrest, just three weeks after admission. Discussion: The present case is remarkable for age and gender of the patient as well as the rapid onset and fast worsening of symptoms, which were related to secondary heart amyloid deposition. Symptoms associated to cardiac amyloidosis are expressions of right heart involvement. The early good results of the therapy did not turn the evolution of disease. The fatal and overwhelming progression of the myocardial involvement led to the patient's death in less than one month.